The Berenstain Bears and the slumber party - Berenstain, Stan, 1923-; Berenstain, Jan, 1923- (New York : Random House, 1990)
Lizzy Bruin's slumber party becomes even wilder when Too- Tall Grizzly and his friends decide to attend uninvited.
AD 680
Adult 680
Accelerated Reader AR
Keywords: Bears -- Fiction; Parties -- Fiction; Behavior -- Fiction